Google and the digital divide : the biases of online knowledge - Segev, Elad (Chandos internet series., 2010)
Beneficial to scholars and students in the fields of media and communication, politics and technology, this book outlines the significant role of search engines in general and Google in particular in widening the digital divide between individuals, organisations and states. It uses innovative methods and research approaches to assess and illustrate the digital divide by comparing the popular search queries in Google and Yahoo in different countries as well as analysing the various biases in Google News and Google Earth.